Measuring and Improving Project Management Governance: A Case Study in a Brazilian Public Company - Oliveira, Nathan Peixoto; Jesus, Rômulo Henrique Gomes de; Rodrigues, Thales Volpe (Gestão e Desenvolvimento em Revista, 2020)
In a recent scenario of corporate breakdown, fiscal scandals and lack of integrity of multinationals, the governance theme has been receiving great repercussion and prominence. Thus, stakeholders have increasingly assumed the role of charging for transparency and corporate performance. A great ally to achieve its strategic objectives has been governance in project management, still incipient and with improvements to be achieved. Thus, this paper proposed to present a model for analysis, measurement and continuous improvement in this subject. Through a case study at a government fiscal public company, issues were raised under four project perspectives (portfolio management, project sponsorship, project management capability and disclosure and reporting), drawing a real profile of the company and creating an action plan to develop its governance in projects. The relevance of this study was justified by the use of an easily applicable tool, adaptable to any sector in which the institution is inserted.